Dietary Pattern Indices and Incident Peripheral Arterial Disease in Women: A Prospective Cohort Study. (29th May 2020) - Chen, Guochong; Mossavar-Rahmani, Yasmin; Xue, Xiaonan; Haring, Bernhard; Shadyab, Aladdin; Allison, Matthew; Liu, Simin; Tinker, Lesley; Saquib, Nazmus; Coday, Mace; Shikany, James; Neuhouser, Marian; et al.
Abstract: Objectives: We aimed to evaluate diet quality as reflected by multiple a priori dietary pattern indices in relation to incident PAD. Methods: We included 138, 506 US postmenopausal women aged 50–79 years without known PAD at baseline (1993–1998) of the Women's Health Initiative. Score of 4 dietary pattern indices, including the alternate Mediterranean diet (aMED) index, the alternate Healthy Eating Index (AHEI)-2010, the Dietary Approaches to Stop Hypertension (DASH) diet index, and the Healthy Eating Index (HEI)-2015, were derived using data collected by a validated food frequency questionnaire. Incident cases of symptomatic PAD in the lower extremities were ascertained and adjudicated through March 2019 by reviewing medical record. Hazard ratios (HR) and 95% confidence interval (CI) were estimated using Cox proportional hazards models, with adjustment for multiple potential confounders including known risk factors for PAD (i.e., smoking, high blood pressure, dyslipidemia, and diabetes). Results: During a median 18.6 years of follow-up, 1036 incident cases of PAD were identified. All 4 dietary pattern indices were inversely associated with risk of PAD. The multivariable-adjusted HRs (95% CI) comparing the highest with the lowest score quartiles were 0.74 (0.61–0.91) for aMED index (P-trend across quartile = 0.010), 0.79 (0.65–0.95) for AHEI-2010 (P-trend < 0.001), 0.66 (0.55–0.80) for DASH index (P-trend < 0.001), and 0.68 (0.56–0.82) for HEI-2015 (P-trend < 0.001). Among major foods/nutrients contributing to these dietary patterns, intakes of whole grains (top vs. bottom quartile, HR = 0.81; P-trend = 0.01), legumes (HR = 0.77; P-trend = 0.004), dietary fiber (HR = 0.78; P-trend = 0.01), and vegetable protein (HR = 0.76; P-trend = 0.006) were associated with lower risk of PAD, whereas intakes of red meat (HR = 1.38; P-trend = 0.003), processed meat (HR = 1.36; P-trend = 0.004), and regular soft drinks (HR = 1.26; P-trend = 0.01) were associated with higher risk. Conclusions: Adherence to various recommended dietary patterns is associated with lower risk of PAD in a nationwide cohort of US postmenopausal women. Our findings may extend the range of cardiovascular diseases that are potentially preventable by adopting a healthy dietary pattern. Funding Sources: National Heart, Lung, and Blood Institute; and National Institute of Diabetes and Digestive and Kidney Diseases.